Non‐invasive in vivo imaging by confocal laser scanning microscopy of gingival tissues following natural plaque deposition. (4th February 2014) - Eberhard, Jörg; Loewen, Hendrik; Krüger, Alexander; Donner, Sabine; Stumpp, Nico; Patzlaff, Mandy; Stachs, Oliver; Reichard, Maria; Ripken, Tammo; Heisterkamp, Alexander; Stiesch, Meike
Abstract Aim Imaging with Confocal Laser Scanning Microscopy (CLSM) generates high‐resolution images and may be well suited for basic research in Periodontology and Implant Dentistry. The present study was aimed to explore the in vivo application of CLSM in experimentally induced gingivitis. Materials and Methods Ten subjects were recruited and were advised to stop any oral hygiene of the upper front teeth for 7 days. The gingival tissues were observed using a Heidelberg Retina Tomograph combined with a Rostock Cornea Module at baseline and day 7. The system used a laser of 670 nm and the contrast was given by backscattering from different tissues. Each examination created 800–1200 images that were descriptively analysed. Results After 7 days of abandoned oral hygiene, plaque scores and bleeding frequencies increased. By using CLSM images tooth hard substances, cells and plaque deposits were distinguishable. Increased epithelial cell irregularities, the apical migration of the sulcular epithelium, cellular infiltrates within the sulcus and plaque deposits were observed at day 7. Conclusions The present study showed for the first time that CLSM is suitable for in vivo imaging of the gingival sulcus and adjacent tissues.